Lip cavernous hemangioma in a young child - Avila,Érica Dorigatti de (2010)
Hemangiomas are benign tumors of infancy and childhood, characterized by a phase of fast growth with endothelial cell proliferation, occurring in 10-12% of children at 1 year of age. It is known that hemangiomas of infancy are most commonly located on the head and neck region (around 60% of cases) and occur more frequently in the lips, tongue, and palate. Approximately 50% of hemangiomas have complete resolution, and 90% of them are resolved up to the age of 9. Complications occur in only 20% of the cases, the most common problem being ulceration with or without infection. The treatment depends on lesion location, size and evolution stage, and the patient's age. Surgery is usually indicated when there is no response to systemic treatments, or even for esthetic reasons, being performed as a simple excision in combination or not with plastic surgery. This paper reports a case of lip cavernous hemangioma in a 4-year-old child, who was submitted to 3 sessions of vascular sclerosis due to the size of the lesion, before undergoing simple excision of the hemangioma. Two years of postoperative clinical follow-up shows treatment success with no recurrence of the lesion.